2009
DOI: 10.1088/0004-637x/701/2/1015
|View full text |Cite
|
Sign up to set email alerts
|

A SPECTROSCOPIC CENSUS OF THE M82 STELLAR CLUSTER POPULATION,

Abstract: We present a spectroscopic study of the stellar cluster population of M82, the archetype starburst galaxy, based primarily on new Gemini-North multi-object spectroscopy of 49 star clusters. These observations constitute the largest to date spectroscopic dataset of extragalactic young clusters, giving virtually continuous coverage across the galaxy; we use these data to deduce information about the clusters as well as the M82 poststarburst disk and nuclear starburst environments. Spectroscopic age-dating places… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 52 publications
(67 reference statements)
7
94
3
1
Order By: Relevance
“…The stellar clusters in the center of M 82 are estimated to be the result of starbursts from at least ∼ 10 − 15 Myr ago, as seen at optical wavelengths by Konstantopoulos et al (2009). This value indicates that we are seeing a more evolved starburst (or post-starburst) in M 82, older than the NGC 253 and IC 342 ones (we are not aware of a published stellar population age in the center of Maffei 2).…”
Section: Evolved Starburst: M 82mentioning
confidence: 87%
“…The stellar clusters in the center of M 82 are estimated to be the result of starbursts from at least ∼ 10 − 15 Myr ago, as seen at optical wavelengths by Konstantopoulos et al (2009). This value indicates that we are seeing a more evolved starburst (or post-starburst) in M 82, older than the NGC 253 and IC 342 ones (we are not aware of a published stellar population age in the center of Maffei 2).…”
Section: Evolved Starburst: M 82mentioning
confidence: 87%
“…According to Yun's simulation (Yun 1999), M81 underwent the closest passage about 220 and 280 Myr ago by its companion galaxies M82 and NGC 3077, respectively. In addition, many observational studies (e.g., Yun et al 1994;Chandar et al 2001;Pérez-González et al 2006;de Mello et al 2008;Konstantopoulos et al 2009;Santiago-Cortés et al 2010;Hoversten et al 2011;Lim et al 2013) have found evidence for tidally induced SF in both M81 and its companion galaxies: ages of compact star clusters and star-forming regions range ∼100-500 Myr. Although we also detected enhanced SF at ages between 200 and 350 Myr in all 20 regions, the associated systematic errors are significant since the stars sensitive to this SF peak are near the 50% completeness limit of the data, and therefore this result would require additional observations to confirm with confidence.…”
Section: Tidally Induced Grand-design Spiral Arm?mentioning
confidence: 99%
“…However, the ongoing nuclear starbursts started ∼15 Myr ago, with nuclear star clusters dated between 7 and 15 Myr (Konstantopoulos et al 2009). This dating agrees with the two short-duration bursts of star formation in the nuclear region of M 82, with peaks at 5 and 10 Myr (Förster Schreiber et al 2003).…”
Section: Chemical Evolution Of Starburst Galaxiesmentioning
confidence: 99%
“…However, this fast evolution might also result in an overproduction of 18 O , which is not observed. Moreover, if the timescale of the main burst in the nucleus of M 82 is less than 15 Myr (Förster Schreiber et al 2003;Konstantopoulos et al 2009), then most of the 12 C enriched material would be in the hot outflow with a contribution to the molecular gas. The timescale is rather short to have the 12 C enriched material well mixed over the ∼300 pc of our beam size, in both M 82 and NGC 253.…”
Section: Chemical Evolution Of Starburst Galaxiesmentioning
confidence: 99%